134 Racial Disparities in Healthcare Resource Utilization After Pediatric Cervical and/or Thoracic Spinal Injuries: Is it Black and White?. (1st April 2022) - Elsamadicy, Aladine A.; Sandhu, Mani; Freedman, Isaac G.; Koo, Andrew B.; Hengartner, Astrid; Reeves, Benjamin; Havlik, John; Sarkozy, Margot; Kundishora, Adam; Tuason, Dominick; DiLuna, Michael
Abstract : INTRODUCTION: Racial disparities ubiquitously pervade the United States healthcare system. While there have been efforts to look at racial disparities in adult spinal trauma, there exists a paucity of data in pediatrics. METHODS: A retrospective cohort was performed using the 2017 admission year from 753 facilities. All pediatric patients (1-17 years) with cervical and/or thoracic spine injuries were identified using the International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) diagnosis coding system. These patients were dichotomized by their race, either African American/Black or Caucasian/White. Demographic, comorbidiites, and injury presentations were collected. The total length of hospital stay, length of ICU stay, total days on ventilator, and hospital complications were also collected. A linear and logistic multivariate regression analysis was performed to determine the risk-ratio for hospital LOS as well as complication rate, respectively RESULTS: A total of 3, 187 pediatric patients were identified, 637 were African-American (AA) and 2, 550 were White (W). Compared to White patients, African-American cohort had a greater prevalence of cervical-only injuries (AA: 50.39% vs W: 37.18%, p < 0.001). While transport accident was most common injury etiology for both cohorts, African-American cohort had a greater prevalence of assault (AA: 18.05% vs W: 1.61%, p < 0.001) than White cohort. Overall complication rates were significantly higher among African-American patients (AA: 15.38% vs W: 9.33%, p < 0.001). Compared to their White counterparts, African-American patients had a 3.4 day longer mean hospital LOS (AA: 9.6 ± 21.55 days vs W: 6.23 ± 9.13 days, p < 0.001) and a 1.7 day longer mean ICU LOS (AA: 4.42 ± 9.98 days vs W: 2.69 ± 6.53 days, p < 0.001). African-American race was identified as a significant predictor of increased LOS on multivariate regression analysis [RR: 1.27, CI (0.52, 2.03), p < 0.001] but not hospital complications (p = 0.286). CONCLUSION: Our study demonstrates that race may have a significant impact on healthcare resource utilization following pediatric cervical and/or thoracic spinal trauma.